Global Leadership Competency and Personality Traits: A Study in Thai Context - Petcharat, Sarit; Rimkeeratikul, Sucharat (วารสารวิชาการ มหาวิทยาลัยนอร์ทกรุงเทพ, 2021)
This study aims to investigate the trait components of global leadership competency (GLC) as additional guidelines for a self-assessment of Thai foreign relations officers (FRO). Participants in the study were 54 FRO from 16 ministries and two independent organizations in Thailand. The study employed a quantitative method using a self-report questionnaire to collect data on the leadership traits and intercultural competence traits which are considered key components of GLC. Pearson’s correlation revealed that leadership traits and intercultural competence traits are interdependent and can be used as variables for investigating GLC. Exploratory factor analysis was used to combine and regroup the leadership traits and intercultural competence traits to explore the trait components of GLC in the Thai context. Findings revealed that there were eight trait components, as follows: goal-oriented, mind-oriented, team-oriented, sociability-oriented, progress-oriented, exploration-oriented, self/other-oriented, and global-oriented.